Double Thyroglossal Duct Cysts in an Adult. Issue 1 (January 2017) - Lee, Dong Hoon; Yoon, Tae Mi; Lee, Joon Kyoo; Lim, Sang Chul
Abstract : Abstract: Double thyroglossal duct cysts (TDCs) are a very rare congenital malformation. Herein, we report a rare case of double TDCs, one below the hyoid bone and the other at the base of the tongue. Clinicians should be aware that TDCs can occur as multiple cystic lesions. Preoperative radiological examinations should be performed for an accurate diagnosis of double TDCs.